APPROACHING ISSUES OF HUMAN DIGNITY IN A DIGITAL WORLD - Soliev Ikromjon Komiljonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article focuses on the digital health scheme to create a single electronic personal medical record that is available to any doctor. Digitization of public space is imbued with the ideas of personalization and individualization. Man and humanity have been considered as the highest value since time immemorial.